Critical Acceptance Factors towards the Ar-Rahnu Scheme in Malaysia - Nik Azman, Nik Hadiyan; Kassim, Salina (2014)
Of late, there is growing acceptance of ar-rahnu as a viable and competitive mode of financial instrument in the Islamic finance industry. Amid the increasing interest, research efforts have been focused on reviewing and examining ar-rahnu particularly on the acceptance factors of ar-rahnu, but scanty exertion has been given on acceptance factors from the perspective of the customers. Through a thorough review of the literature, this study highlights the important aspects on the customers'acceptance of ar-rahnu in Malaysia.